Epidemiology of HIV-1 Antibody Among Pregnant Women in the Region 12, Thailand (1994) - Phoomborplab, Somsakul (Journal of Health Science of Thailand, 1994)
This study was conducted because the southernmost part of Thailand (region 12) has its own culture, traditional, believe and way of life different from the other parts. The retrospective study on 6,583 pregnant women attending antenatal care clinic at provincial hospitals was carried out in 1994. Result showed that 91 pregnant women were seropositive (1.38 %) of whom 47 (51.65%) were in 20-24 age group, 46 of the cases (50.54%) were primigravida and 20.88% had abortion history. Syphilis seropositive prevalence rate among HIV seropositive pregnant women was 15.38% and syphilis seropositivity was significantly associated with HIV seropositive pregnancy (P—value <0.001).